A new species of Dendrocephalus (Crustacea, Anostraca) from Serra dos Carajás (Pará State, Brasil) - Rogers, D. Christopher; Gomes, João Pedro Corrêa; Vieira, Fabio (Zootaxa, 2012)
Dendrocephalus carajaensis, a new species of fairy shrimp, is described from a single temporary pool in canga deposits on theSerra Sul plateau, Serra dos Carajás region in Brazilian Amazonian forest, Pará State, Brasil. D. carajaensis sp. nov. males arereadily separated from all other Dendrocephalus species except D. brasiliensis and D. spartaenovae by the absence of a spineon the posterioventral surface of the compound eye. This species is separated from D. brasiliensis and D. spartaenovae by theform of the proximal portion of the frontal appendage and the endopodites of the first three thoracopods. This species appears to be endemic to the Serra dos Carajás.